Pendampingan Digital Entrepreneurship Melalui Incubation Process Pada Warga Binaan Pemasyarakatan Perempuan Kelas IIA Kota Medan - Andriansyah, Dedi; Nainggolan, Erlin; Sadewo, Bayu; Purba, Elvirida Lady Angel; Saragi, Suci Meiken; Ananda, Reyvanza Adliva (Universitas Medan Area, 2024)
The Women's Correctional Institution Class IIA Medan City is one of the prisons that carries out the debriefing process during the rehabilitation stage for its prisoners. Various coaching activities help prisoners improve their skills to become more independent and have the skills to face a new life. Based on the hearing with partners regarding the problems faced by the Prisoners of Correction (WBP) Class IIA Medan Women's Prison. Then the solution to the problem is the need for a program that can increase the knowledge and skills of digital business for WBP in developing their abilities and developing products of Class IIA Medan Women's Prison. Therefore, a digital entrepreneurship mentoring program was created through an incubation process approach for WBP of Class IIA Medan Women's Prison as an effort to improve the future quality of life of former WBP with the ability to do digital business. The service activities were carried out from July to September 2023. At the end of the service, it was found that (1) the knowledge of WBP about Digital Business (Cognitive) increased by 90%, the enthusiasm for Digital Business (Affective) increased by 97%, and Digital Business Skills (Psychomotor) increased by 94%.